Structural Estimation of a Model of School Choices: The Boston Mechanism versus Its Alternatives - Calsamiglia, Caterina; Fu, Chao; Güell, Maia (Journal of Political Economy, 2020)
We model household choice of schools under the Boston mechanism (BM) and develop a new method, applicable to a broad class of mechanisms, to fully solve the choice problem even if it is infeasible via the traditional method. We estimate the joint distribution of household preferences and sophistication types, using administrative data from Barcelona. Counterfactual policy analyses show that a change from BM in Barcelona to the deferred-acceptance mechanism would decrease average welfare by €1,020, while a change to the top-trading-cycles mechanism would increase average welfare by €460.